Evaluation of sustainable development strategies in the mining sector - Stobart, Brandon Ian (My University, 2011)
Formulating, implementing, measuring and reporting on sustainable develoment strategies presents a range of challenges to companies in the South African mining sector. This study evaluates the performance of South African mining companies against standards identified both in the relevant literature and in international practice. In-depth semi-structured interviews and the relevant documentary evidence were used to obtain input from mining companies, related institutions and consultants in the field of sustainable development...
MBA - WBS
Keywords: Sustainable development; Mines and mining